SEMANTIC ASPECT OF THE LINGUISTIC DESCRIPTION OF LEXICON OF ORTHODOX DOGMA IN CHURCH SLAVONIC LANGUAGE - Sergej Vladimirovich Feliksov (RUDN Journal of Language Studies, Semiotics and Semantics, 2018)
In article one of relevant and not enough studied problems connected with a question of semantic classification of lexicon of orthodox dogma functioning in texts of Church Slavonic language is considered. The author notes that the experiences of semantic division of lexicon of the religious sphere presented in scientific literature more carry applied, than fundamental character. It in many respects is explained by absence from the scientists dealing with this problem, complete approach to consideration of the studied subject. Overcoming methodological unilaterality, lexicon of orthodox dogma in work receives the semantic description as taking into account those values which are recorded at it in lexicographic and text sources of Church Slavonic language, and with a support on extralinguistic factors. Such approach allowed to develop, according to the author, the accurate bases for semantic division of religious language units and to develop the universal classification scheme allowing to describe all that variety of lexicon of orthodox dogma which exists in Church Slavonic language on its base. Defining the teoretiko-practical importance of the results received during the research, in work it is noted that the submitted solution of a linguistic problem can be used in the methodical purposes when writing education guidances on Church Slavonic language and also it will be useful by drawing up the semantic dictionary of religious lexicon.